Does the denomination taste better than the wine?. Issue 12 (21st October 2019) - Vecchio, Riccardo; Rinaldi, Alessandra; Moio, Luigi
Abstract : Purpose: The purpose of this paper is twofold: first, to investigate whether consumer preferences differ for wines with diverse price points and second, to analyze the effect of denominations of origin information on preferences. Design/methodology/approach: In, total 150 regular wine buyers expressed their willingness-to-pay (WTP) for 12 red wines of 3 denominations (Chianti Classico DOCG, Morellino di Scansano DOCG and Toscana IGT) with three price points (basic=€5, medium=€10 and high=€20) in an incentive-compatible experiment, involving two consecutive rounds: a blind tasting and an informed tasting. Findings: The findings reveal that price points are not statistically related to consumer preferences measured in the blind round, while information on the denomination of origin leads to a statistically significant increase in WTP for wines of all price points for all denominations. Originality/value: This paper investigates whether Sangiovese-based wines at varying levels of price points (basic, medium and high) receive different WTP by consumers in non-hypothetical experimental auctions. Furthermore, the effect of denominations of origin information on preferences is explored, comparing evaluations without and with this specific information.